(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed to investigate the employment of electronic supervision applications in developing the teaching performance of teachers in Oman. Based on the qualitative method and the study population consisted of all the teachers of the first cycle in the Governorate of Muscat. The study sample amounted to 24 female teachers. The interview was used as a tool for data collection. The study reached several results, including: There are difficulties in employing electronic supervision applications, which are weak network, density of curricula, lack of experience in applying technology, and the large number of tasks assigned to the teacher. These difficulties can also be overcome by strengthening the network, training teachers, reducing the intensity of the curriculum, and placing the teacher in teaching only. The study also revealed that employing electronic supervision applications helps in developing the teacher’s performance. The study recommended the establishment of an electronic platform for electronic supervision.